From Dawn till Dusk: Implications of Full-Day Care for Children's Development - Christina Felfe; Larissa Zierow (Center for Economic Studies and ifo Institute (CESifo), 2017)
A currently high-ranking question on the political agenda of many developed countries relates to the intensive margin of child care and thus to the effects of prolonging the opening hours of child care institutions. This study adds to the scarce literature on this question and investigates the consequences of expanding the supply of child care centers operating on a fullday basis on children's skill development just before entering primary school. Identification relies on a substantial expansion of the number of full-day slots triggered by reforms of the German child care system. Using unique administrative data covering almost 100'000 children, we find positive effects on immigrant children's school readiness. Yet, at the same time immigrant children suffer in terms of their socio-emotional development, a finding we also observe among native children from disadvantaged family backgrounds.
Keywords: J13; I21; I38; 330; child care; child development